The impact of channel fin width on electrical characteristics of Si-FinFET - Yousif Atalla; Yasir Hashim; Abdul Nasir Abd. Ghafar (Institute of Advanced Engineering and Science, 2022)
This paper studies the impact of fin width of channel on temperature and electrical characteristics of fin field-effect transistor (FinFET). The simulation tool multi-gate field effect transistor (MuGFET) has been used to examine the FinFET characteristics. Transfer characteristics with various temperatures and channel fin width (WF=5, 10, 20, 40, and 80 nm) are at first simulated in this study. The results show that the increasing of environmental temperature tends to increase threshold voltage, while the subthreshold swing (SS) and drain-induced barrier lowering (DIBL) rise with rising working temperature. Also, the threshold voltage decreases with increasing channel fin width of transistor, while the SS and DIBL increase with increasing channel fin width of transistor, at minimum channel fin width, the SS is very near to the best and ideal then its value grows and going far from the ideal value with increasing channel fin width. So, according to these conditions, the minimum value as possible of fin width is the preferable one for FinFET with better electrical characteristics.